Sexual Harassment in Film Penyalin Cahaya - Balkis Nur Azizah; Akhmad Muzakki; Ahmad Kholil (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Research on sexual harassment is becoming a hot topic because data shows that crimes of sexual harassment are increasing every day. This study aims to show the form of patriarchy and the impact of patriarchy in the film Penyalin Cahaya using radical feminism theory. The researcher uses a qualitative descriptive research method with the primary data source of the film Penyalin Cahaya. Data collection techniques are carried out by listening to and recording related data. The results of this study found that there were six forms of patriarchy form of modes of production, patriarchy in jobs with wages, patriarchy in the state, male violence, patriarchy in sexuality, and patriarchy in institutions. The patriarchal influence in the film Penyalin Cahaya includes positive impacts, namely hard work and solidarity, while adverse effects include losing scholarships, stealing data, and promiscuity.